Hubungan Kekuatan Otot Tungkai Terhadap Kemampuan Passing Futsal Di SMA Negeri 6 Bengkulu Selatan - Raharja, Ranten; Sembiring, Lina Tri Astuty Beru; Anggara, Deffri (Educative Sportive, 2024)
This study aims to determine the relationship between leg muscle strength and futsal passing ability at SMA Nengeri 6 South Bengkulu. The type of research used is quantitative with a correlation research method. The research population was all futsal extracurricular students at SMA Negeri 6 Bengkulu Selatan, totalling 20 students. The sample of this study were futsal extracurricular students at SMA Negeri 6 Bengkulu Selatan who were taken with total sampling technique with a total of 20 students. The research instrument used was an experiment. Data collection techniques were carried out with leg muscle strength tests and passing ability tests. Data analysis techniques in this study using product moment correlation calculations. The results of this study indicate that the correlation coefficient is 0.93 with a significance level of 5% and n = 20, then the table is 0.444. So that the obtained rcount> rtable, namely 0.93> 0.444, with the contribution of variable X to variable Y by 86.49%. It can be concluded that there is a relationship between leg muscle strength and futsal passing ability at SMA Negeri 6 Bengkulu Selatan.